2017
DOI: 10.1177/2048872617737041
|View full text |Cite
|
Sign up to set email alerts
|

Effects of extracorporeal cardiopulmonary resuscitation on neurological and cardiac outcome after ischaemic refractory cardiac arrest

Abstract: Extracorporeal cardiopulmonary resuscitation patients are younger and have less comorbidities than conventional cardiopulmonary resuscitation, but they have worse survival and lower early left ventricular ejection fraction. Survivors after extracorporeal cardiopulmonary resuscitation have a neurological outcome and recovery of heart function comparable to subjects with return of spontaneous circulation. Total cardiac arrest time is the only predictor of survival after cardiopulmonary resuscitation in both grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 32 publications
(53 reference statements)
0
27
0
Order By: Relevance
“…Twenty-five observational studies met all of the inclusion criteria and none of the exclusion criteria. [1640] Fifteen studies were in adult OHCA [1630], 7 studies were in adult IHCA [3137], and 3 studies were in pediatric IHCA [38,1740]. We identified no studies in pediatric OHCA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-five observational studies met all of the inclusion criteria and none of the exclusion criteria. [1640] Fifteen studies were in adult OHCA [1630], 7 studies were in adult IHCA [3137], and 3 studies were in pediatric IHCA [38,1740]. We identified no studies in pediatric OHCA.…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen of the included studies were in adult OHCA [1630]. Eight studies were performed in Asia [1822,24,26,27], 4 studies in Europe [16,17,23,25], and 3 studies in North America [28,1730]. Three studies included both OHCA and IHCA patients [17,21,28].…”
Section: Resultsmentioning
confidence: 99%
“…82,89,99 Most studies defined the exposure as ECPR use; 1 study93 defined the exposure as ECPR availability; and 2 studies 100,101 defined the exposure as an ECPR strategy. Twelve studies reported survival to hospital discharge 80,82,85,87À89,91À93,97À99 ; 6 studies reported long-term survival 82,88,91,93,97,98 ; 8 studies reported favorable neurological outcome at hospital discharge 85,87,88,92,93,97,100,101 ; and 6 studies reported long-term favorable neurological outcomes. 88,91,93,94,97,98 Seven of the included studies were in adult IHCA.…”
Section: Consensus On Sciencementioning
confidence: 99%
“…An analysis of neonatal and pediatric ECPR events from a multicenter, national registry showed that while only 43.7% of patients survived to hospital discharge, the majority of survivors had favorable neurologic outcomes [27]. Another study comparing survivors of ECPR and those with return of circulation after conventional CPR found comparable neurologic outcomes between the two groups, with total duration of cardiac arrest being the only predictor of survival [28].…”
Section: Extracorporeal Cardiopulmonary Resuscitation (Ecpr)mentioning
confidence: 99%